The Returns to English-Language Skills in India - Mehtabul Azam; Aimee Chin; Nishith Prakash (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
India's colonial legacy and linguistic diversity give English an important role in its economy, and this role has expanded due to globalization in recent decades. It is widely believed that there are sizable economic returns to English-language skills in India, but the extent of these returns is unknown due to lack of a microdata set containing measures of both earnings and English ability. In this paper, we use a newly available data set - the India Human Development Survey, 2005 to quantify the effects of English- speaking ability on wages. We find that being fluent in English (compared to not speaking any English) increases hourly wages of men by 34%, which is as much as the return to completing secondary school and half as much as the return to completing a Bachelor's degree. Being able to speak a little English significantly increases male hourly wages 13%. There is considerable heterogeneity in returns to English. More experienced and more educated workers receive higher returns to English. The complementarity between English skills and education appears to have strengthened over time. Only the more educated among young workers earn a premium for English skill, whereas older workers across all education groups do.
Keywords: J31; J24; O15; 330; English Language; Human Capital; India